Tantangan Penegakan Hukum terhadap Politik Uang di Indonesia: Studi Kasus dan Perspektif Internasional - Suwandi; Sulastri; Nurdiyana; Hanafi, Imam (Indonesian Journal of Law and Justice, 2024)
Political money is a significant issue threatening the integrity of elections inIndonesia, often hindering the democratic process and violating principles of justice. Law enforcement againts political money in Indonesia faces various challenges, including ambiguous regulations and inadequate supervision. This study aims to analyze the challenges in law enforcement againts political money in Indonesia and compare the implementation of such laws with other countries. The method employed is qualitative analysis using a case study approach, utilizing relevant literature, government reports, and international studies. The findings show that, althought regulations on political money exist, weak implementation and supervision remain the main obstacles in Indonesia. Additionaly, a comparison with countries such as Singapore and the United States reveals the success of combating political money through stricter legal systems and more effective oversight. This study offers recomemendations to strengthen law enforcement and increase public participation in monitoring political money practices.